Efficiency of Antibacterial Suture Material in Cardiac Surgery: A Double-Blind Randomized Prospective Study - (:unkn) unknown (FORUM MULTIMEDIA PUBLISHING, LLC, 2012)
Objective: Postoperative surgical site infections (SSI) still greatly affect mortality and morbidity in cardiovascular surgery. SSI may be related to the suture material. In this prospective, randomized, controlled, and double-blinded study, the effect of antibacterial suture material on SSI in cardiac surgical patients was investigated. Methods: We randomly allocated 510 patients into 2 groups. Antibacterial suture materials were used for wound closure in 170 patients (triclosan-coated suture group), and routine suture materials were used in 340 patients (noncoated suture group). All patients were evaluated for SSI on days 10, 20, and 30 following cardiac surgery. Results: Preoperative risk factors and laboratory findings were comparable for the 2 groups. Sternal infection occurred in 4 (2.4%) of the patients in the triclosan-coated suture group and in 3.5% of the noncoated suture group (P > .05). Leg wound infection occurred in 5 (3.5%) of the patients in the triclosan-coated suture group and in 3.8% of the noncoated suture group (P > .05). Only diabetes mellitus was an independent predictor of SSI. Conclusion: Both noncoated and triclosan-coated suture materials are safe. Larger studies may be needed to show the benefit and cost-effectiveness, if any, of triclosan-coated materials over noncoated materials.
Keywords: SURGICAL-SITE INFECTIONS; RISK-FACTORS; LEG; RATES